Exposure to pesticides and cancer: integrative literature review (Research, Society and Development, 2023)
It is a consensus of the scientific community that the excessive use and ingestion of pesticides is a public health issue. The aim of this study was to analyze evidence from the literature on exposure to pesticides and cancer. This is an integrative literature review, conducted from January to March 2023. The data collection resulted in 8 articles from the LILACS, BDENF and MEDLINE databases. The analyzed studies are mostly of a quantitative approach, published between the years 2015 to 2020, carried out in different countries and address the occurrence of cancer in people who use pesticides. There is evidence that this type of exposure is associated with the non-use of personal protective equipment, as well as the lack of use of sunscreen and the lack of technical information on the correct handling of chemical products. The coefficient of morbidity from cancer is higher in individuals residing in rural areas, a fact related to the exaggerated application of pesticides in agricultural production. However, most rural workers report that they are aware of the risks that pesticides cause to human health. Therefore, the nurse must develop promotion and prevention actions for the population in contact with pesticides, allowing the safe use of these chemical products in the work process.